Exploring the influence of visual content quality marketing on impulse buying in tiktok shop the mediating role of copywriting - Made Putri Ariasih; Ni Luh Laksmi Rahmantari; Gede Surya Mahendra (Institute of Computer Science (IOCS), 2023)
This study aims to examine the extent of the influence of visual content quality in marketing on impulse buying on TikTok Shop, mediated by copywriting. The study will employ a causal design approach as a statistical approach to test the constructs and hypotheses developed. The sample size for this study is 110 respondents across Bali who actively use TikTok Shop as their shopping platform. The research findings indicate that visual content quality in marketing does not have a direct significant effect on increasing impulse buying. However, copywriting effectively mediates the relationship between visual content quality in marketing and impulse buying. This research provides valuable insights into the importance of high-quality visual content, the role of copywriting, and their relationship with impulse buying. The implications and contributions of this research can help enhance understanding and marketing practices in the era of online social commerce platforms like TikTok Shop.